2007
DOI: 10.1002/prot.21390
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional characterization of binding sites in metallocarboxypeptidases based on Optimal Docking Area analysis

Abstract: The metallocarboxypeptidases (MCPs) belonging to the clan MC were studied by the Optimal Docking Area (ODA) method to evaluate protein-protein binding sites and to provide a basis for the identification of binding partners for this class of enzymes. The ODA method identifies surface patches with optimal desolvation energy based on the selection of low-energy docking regions, generated from a set of surface points around the protein. With few exceptions, the ODA method identified surface patches with a signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…dimensional structures of the M14 family of CPs that were the subject of a recent structural and functional characterization of binding sites using this method (Fernandez et al, 2007). In the mentioned study it was found that although the set of CPenzyme domains were structurally very similar, the protein-protein docking surfaces of different subclasses differed substantially and could be distinguished based on analysis of ODA residues over the surface of the protein.…”
Section: Figurementioning
confidence: 96%
See 2 more Smart Citations
“…dimensional structures of the M14 family of CPs that were the subject of a recent structural and functional characterization of binding sites using this method (Fernandez et al, 2007). In the mentioned study it was found that although the set of CPenzyme domains were structurally very similar, the protein-protein docking surfaces of different subclasses differed substantially and could be distinguished based on analysis of ODA residues over the surface of the protein.…”
Section: Figurementioning
confidence: 96%
“…To identify continuous surface patches with optimal desolvation energy, we followed the procedure established in a previous publication (Fernandez et al, 2007). Briefly, a number of starting points were defined around the protein using the centre of coordinates of each residue side chain.…”
Section: Calculation Of Oda Patchesmentioning
confidence: 99%
See 1 more Smart Citation
“…70 The strategy has been applied to numerous cases of biological and therapeutic interest, with excellent predictive results. [71][72][73][74]…”
Section: Computational Prediction Of Protein-protein Interfacesmentioning
confidence: 99%
“…In green is shown the contour of the real interface (if known) for comparison purposes. Positive predictive values of the predictions are 60, 80, 87, 90, and 90%, from left to right and top to bottom, respectively 94…”
Section: Introductionmentioning
confidence: 97%